SPONTANEOUS PORTOSYSTEMIC SHUNTS: RELATIONSHIP TO UPPER GASTROINTESTINAL BLEEDING AND HEPATIC ENCEPHALOPATHY - Atilla ÖKTEN; Sabahattin KAYMAKOĞLU; Süleyman YALÇIN; Oktay YEĞİNSU and Fatih BEŞIŞIK and Arif ACAR and Güngör BOZTAŞ and Yılmaz ÇAKALOĞLU and Zeynel MUNGAN and Sadakat ÖZDİL (Turkish Journal of Gastroenterology, 2020)
-